Nutritional interventions for oral mucositis: a systematic literature review. Issue 1 (4th February 2021) - Edwards, Anna; Santos, Claire; Chen, An‐Yang; Bauer, Judith
Abstract: Aim: Oral mucositis is a debilitating side‐effect of conventional cancer treatment, particularly of the head and neck region. This review aimed to evaluate existing evidence to identify optimal nutritional interventions for oral mucositis management in adult populations receiving treatment for cancer. Methods: CINAHL, PubMed, Embase and Scopus were searched from database inception to July 2019, with each eligible article critically appraised for risk of bias and assigned a quality rating. Certainty of evidence was appraised using the Grading of Recommendations, Assessment, Development and Evaluation system. Results: Twenty‐three articles were identified (total unique study participants n = 7605). Nine intervention areas were identified. Certainty of evidence was moderate for oral cryotherapy in patients with solid or haematological cancers receiving 5‐Fluorouracil or high‐dose Melphalan chemotherapy prior to haematopoietic stem cell transplantation; and low for zinc supplementation for patients with oral cancer undergoing radiotherapy or chemoradiotherapy. Moderate certainty of evidence exists to recommend against glutamine supplementation in all cancer patients. Conclusion: Research must determine the safety and efficacy of identified interventions to guide clinical practice. Addressing limitations requires larger, higher‐quality trials to increase evidence certainty.